Interpreting the Clinical Significance of Capacity Scores for Informed Consent in Alzheimer Disease Clinical Trials - Karlawish, Jason (2008)
OBJECTIVE: Among Alzheimer disease (AD) patients enrolled in a clinical trial, the authors assessed the ability of a standardized capacity assessment procedure to identify persons who are capable of giving their own informed consent. DESIGN: Cross-sectional interview. SETTING: Thirteen sites participating in a randomized and placebo controlled study of simvastatin for the treatment of mild to moderate AD. PARTICIPANTS: Persons with mild to moderate AD and their study partners enrolled in the simvastatin clinical trial. MEASUREMENTS: Interviews to assess decision-making capacity using the MacArthur Competency Assessment Tool for Clinical Research (MacCAT-CR). RESULTS: Judges blinded to the subject’s clinical status had a high rate of agreement on patients capable of giving their own informed consent (κ = 0.73). The understanding subscale had the best receiver operator characteristic and an analysis of positive and negative predictive values over a range of hypothetical prevalences of incapacity to consent demonstrated the value of a range of understanding cut-points. CONCLUSION: Among mild to moderate AD patients, enrolled in an actual clinical trial, these results suggest evidence based guidelines for using the MacCAT-CR understanding subscale to help guide judgments about whether a patient has the capacity to consent.